2008
DOI: 10.1080/14783360701591978
|View full text |Cite
|
Sign up to set email alerts
|

A performance evaluation model of CRM on non-profit organisations

Abstract: Recently, CRM (Cause-Related Marketing) has gradually been adopted by non-profit organisations. However, for the evaluation of CRM's effect, a non-profit organisation still refers to traditional financial data, which could not understand the influence and effect of CRM on a non-profit organisation completely. This research introduces the concept of the Balanced Scorecard as the framework for the evaluation of CRM, and utilises the Balanced Scorecard's five dimensions in a non-profit organisation to design a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…Successful performance results from goal achievement and project implementation (Wu and Hung, 2008). Methods for assessing performance evolve along with advances in technology and growing market demands.…”
Section: Introductionmentioning
confidence: 99%
“…Successful performance results from goal achievement and project implementation (Wu and Hung, 2008). Methods for assessing performance evolve along with advances in technology and growing market demands.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have also demonstrated that eCRM usage can improve firm revenues, internal processes, learning and overall performance (Coltman 2007;Richard et al 2007;Wu and Hung 2008) as well as salespeople's productivity and call center agents' job performance (Ahearne et al 2007;Jelinek et al 2006;McNally 2007). Some authors have also demonstrated that eCRM usage can positively influence the product development process (Shahin and Nikneshan 2008;Vilaseca-Requena et al 2007).…”
Section: Moderating Role Of Ecrm Usagementioning
confidence: 90%
“…The performance evaluation is a systematic review process carried out to help an organization reach a certain goal. Making performance evaluation part of the management and control system helps the organization to effectively manage its resources and measure its performance in relation to its goals (Wu and Hung, 2008). Pinero (2001) the balanced scorecard approach is aimed at helping the organization achieves its goals, while maintaining the traditional financial perspective to measure its tangible assets.…”
Section: Proposed Gscm Criteriamentioning
confidence: 99%